2006
DOI: 10.1016/j.freeradbiomed.2006.09.006
|View full text |Cite
|
Sign up to set email alerts
|

7-Dehydrocholesterol enhances ultraviolet A-induced oxidative stress in keratinocytes: Roles of NADPH oxidase, mitochondria, and lipid rafts

Abstract: Long wavelength solar UVA radiation stimulates formation of reactive oxygen species (ROS) and prostaglandin E 2 (PGE 2 ), which are involved in skin photosensitivity and tumor promotion. High levels of 7-dehydrocholesterol (7-DHC), the precursor to cholesterol, cause exaggerated photosensitivity to UVA in patients with Smith-Lemli-Opitz syndrome (SLOS). Partially replacing cholesterol with 7-DHC in keratinocytes rapidly (<5 min) increased UVA-induced ROS, intracellular calcium, phospholipase A 2 activity, PGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 66 publications
1
48
0
Order By: Relevance
“…Cholesterol ensures the correct structure and function of the glycolipid-and cholesterol-enriched lipid rafts, where the receptors, and the associated protein kinases, can move and cluster. The final effect will be the control of the intracellular signal transduction (28). An alteration of the PI3K pathway has recently been reported (29) and we have observed defective ERK1 ⁄ 2 and JNK activation in vitiligo fibroblasts (Picardo, unpublished data).…”
Section: Viewpointsupporting
confidence: 67%
“…Cholesterol ensures the correct structure and function of the glycolipid-and cholesterol-enriched lipid rafts, where the receptors, and the associated protein kinases, can move and cluster. The final effect will be the control of the intracellular signal transduction (28). An alteration of the PI3K pathway has recently been reported (29) and we have observed defective ERK1 ⁄ 2 and JNK activation in vitiligo fibroblasts (Picardo, unpublished data).…”
Section: Viewpointsupporting
confidence: 67%
“…Based on subsequent work by other groups, it is likely that 7DHC or 7DHC metabolites underlie the UVA sensitivity. Chignell et al ( 50 ) showed that the UVA photosensitivity in SLOS might be a result of oxidative stress induced by photolysis of cholesta-5,7,9(11)-trien-3 ␤ -ol or 9-DDHC, and Valencia et al ( 51 ) showed that 7DHC enhances UVA-induced reactive oxidative stress by enhancing free radical-mediated membrane lipid oxidation.…”
Section: Slos Phenotypementioning
confidence: 99%
“…One hypothesis is that 7-DHC and/or its oxidative derivatives, i.e., oxysterols, are biologically active, which may play some role in the pathology of SLOS ( 19,(21)(22)(23)(24). In one recent study, for example, it was reported that high levels of 7-DHC cause exaggerated photosensitivity to ultraviolet (UV) A for SLOS patients ( 24 ). Longwavelength UV irradiation has been shown to activate NADPH -dependent oxidase activity, leading to oxidative stress in human keratinocytes ( 24 ).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…In one recent study, for example, it was reported that high levels of 7-DHC cause exaggerated photosensitivity to ultraviolet (UV) A for SLOS patients ( 24 ). Longwavelength UV irradiation has been shown to activate NADPH -dependent oxidase activity, leading to oxidative stress in human keratinocytes ( 24 ). Similarly, in the rat SLOS model, elevated 7-DHC and formation of lipid peroxides lead to retinal degeneration ( 22,25 ).…”
Section: Immunocytochemistrymentioning
confidence: 99%